Spurious Additional Warming Reconstructed From Borehole Temperatures Corrected for the Effect of the Last Glacial Cycle - Jan Šafanda (Geophysical Research Letters)
Abstract Reconstructions of past ground surface temperature changes from temperature logs conducted in several hundred meter deep boreholes have proved to be a valuable independent source of information on climate variations over the last millennium. The reconstruction techniques have been evolving for more than two decades to extract optimally the climate signal of the last millennium contained in the temperature logs of different length performed in sites with different histories of the Last Glacial Cycle. This paper analyzes the method of the Last Glacial Cycle thermal effect removal from such borehole temperature profiles used by Beltrami et al. (2017, https://doi.org/10.1002/2016GL071317) in reconstructing the last 500 year history. I show that the reported results of additional warming in this period reconstructed from the corrected borehole data for North America are an artifact generated by the correction.